Pengaruh Citra Merek dan Kualitas Produk Sunscreen Azarine terhadap Kepuasan dan Loyalitas Konsumen - Rika Fadhila; Efni Siregar; Desri Wiana; Sarah Rouli Tambunan; Vivianti Novita (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Skincare is a skin care product that has the benefit of maintaining healthy skin and treating various skin problems. Most people in Indonesia consider skincare to be a very important need, this is proven by the significant growth in skincare sales every year. One type of skincare that is popular is sunscreen. One of the local sunscreen brands that is widely used is Azarine. Azarine is a local Indonesian brand that focuses on skin care and body care which was founded in 2002. Azarine was founded by PT. Wahana Cosmetics Indonesia. This research aims to examine the direct and indirect influence of brand image and product quality of Azarine sunscreen on consumer satisfaction and loyalty in a case study of students majoring in Business Administration, Medan State Polytechnic. The research method used in this research is a quantitative method with non-probability sampling techniques. The data sources used are primary data obtained from questionnaires and secondary data obtained from the results of literature studies. The analysis approach used is Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The theory used in this research is the theory of brand image, product quality, consumer satisfaction, and consumer loyalty.